ROLE OF POLYAMINES IN INHIBITION OF ETHYLENE BIOSYNTHESIS AND THEIR EFFECTS ON RICE ANTHER CULTURE DEVELOPMENT - Dewi, Iswari S.; Purwoko, Bambang S. (Indonesian Journal of Agricultural Science, 2008)
The polyamines such as putrescine, spermidine, and sperminewere reported to increase green plant regeneration in rice antherculture. Low response of anther culture of rice sub-speciesindica may be improved with the addition of putrescine in theculture media. Four experiments were conducted to study therole of polyamines in inhibition of ethylene biosynthesis andtheir effects on rice anther culture development. Anthers oftwo subspecies of rice, indica (IR64, Krowal, Jatiluhur) andjaponica (Taipei 309) were cultured onto media supplementedwith putrescine (N6P) and without putrescine (N6). Youngpanicles containing the anthers at mid-to-late nucleatemicrospores were cold pretreated at 5 + 2Â°C and incubated inthe dark for 8 days before the anthers were cultured. Resultsshowed that medium without putrescine produced an earliersenescence of indica rice anther than that of japonica. Theaddition of 10-3 M putrescine into the culture media inhibitedethylene biosynthesis as anther senescence delayed, increasedthe three polyamines contents, and decreased the ACC contentas well as ACC oxydase activity in anther-derived calli. In theanther and anther-derived calli of subspecies indica, the totalpolyamines content was lower (10.14 nM g-1 anther and 8.48 nMg-1 calli) than that of subspecies japonica (12.61 nM g-1 antherand 10.16 nM g-1 calli), whereas the ethylene production washigher (32.31 nM g-1 anther and 2.48 nM g-1 calli) than thejaponica (31.68 nM g-1 anther and 1.76 nM g-1 calli). This studysuggests that application of 10-3 M putrescine in anther cultureof rice subspecies indica improves androgenesis by inhibitingearly senescence of cultured anthers and enhancing embryo orcallus formation from microspores.